Expression of DUSP1, LINC02202, and LINC01554 as a biomarker panel in the diagnosis and prognosis of breast cancer - Khoshnazar, Seyedeh Mahdieh; Kazemi, Mandana; Jahanbani, Parnian; Abed, Mohammad Reza Moghare; Afshoon, Shamim (Medical Journal of Indonesia, 2025)
BACKGROUND Breast cancer is a major global health challenge, with diverse and complex gene expression profiles. Long noncoding RNAs (lncRNAs) have emerged as key regulators of various cancers, including breast cancer. This study aimed to investigate the expression and prognostic value of dual specificity phosphatase 1 (DUSP1), LINC02202, and LINC01554 in breast cancer tissues and explore their association with clinical parameters. METHODS DUSP1, LINC02202, and LINC01554 expression in healthy and breast tumor tissues were compared using in vitro and in silico conditions. In silico conditions examined their association with patient survival and disease prognosis through Kaplan−Meier and receiver operating characteristic curves. In vitro conditions examined the association between their expression and clinical parameters, such as tumor size, disease stage, and disease prognosis. RESULTS Our study found that DUSP1, LINC02202, and LINC01554 were significantly downregulated in breast tumor tissues compared to healthy tissues, as shown by both in vitro and in silico analyses. Their expression levels are also significantly associated with the prognosis of breast cancer. Notably, only LINC02202 expression was significantly correlated with reduced patient survival and tumor size. CONCLUSIONS This study provides novel insights into the expression and function of DUSP1 mRNA, LINC02202, and LINC01554 lncRNAs in breast cancer and identifies potential biomarkers and therapeutic targets for this disease.